Studies on Neotropical crickets: A new Tusked Cricket genus (Orthoptera: Phalangopsidae) from Colombia - Cadena-Castañeda, Oscar J.; Quintana-Arias, Ronald Fernando (Zootaxa, 2024)
Dentoluzara spatulatus n. gen. et n. sp., from the middle lands of the Colombian Andes, is described. This new phalangopsid cricket is distinguished by its asymmetrical mandibles with a basal prolongation in the left one, which is why it is recorded as the first “Tusked Cricket.” This rare morphological structure has only been observed in some species of anostostomatids and a couple of genera of tettigoniids, but never in crickets. Furthermore, D. spatulatus n. gen. et n. sp., has the ps. p2, from the male genitalia, spatula-shaped, deriving its specific epithet from there. Finally, the new genus’ peculiar mandibular morphology and the subfamily Luzarinae’s taxonomy are commented and discussed.